Расчет компонент тензора напряжений на радиусе закругления профилирующего ролика при радиально-ротационном профилировании ободьев колес - Пузырь, Р. Г. (НТУ "ХПИ", 2015)
Рассматриваются вопросы определения поля напряжений при формоизменении ободьев колес из стальных заготовок на первом переходе радиально-ротационного профилирования. Интерес представляет определение напряжений на радиусе закругления профилирующего ролика, так как именно места сопряжений различных элементов профиля обода испытывают во время эксплуатации наибольшие нагрузки. Результаты теоретического исследования позволяют анализировать возникающие в процессе деформирования напряжения и определять совокупность технологических и конструкторских параметров процесса профилирования, которые оказывают значительное влияние на величину и распределение нормальных и касательных напряжений.

The issues of determining the stress field at forming rims of steel billets at the first transition of radial rotary profiling. Of interest is the determination of the stresses on the radius of curvature of the profiling roller, as it is the place of interfaces of the various elements of the rim profile test during operation to maximum loads. The results of theoretical studies allow to analyze the deformation occurring during the voltage and determine a set of technological and design parameters of the profiling process, which have a significant impact on the magnitude and distribution of normal and tangential stresses. Summarizing the results, we can say that the distribution and magnitude of the meridional stresses on the curved sections of the profile of the rim in the process of deformation is influenced by the angle of coverage radius of curvature of the roller and workpiece material θ indicator which is the ratio of the radius of curvature of the profile to the radius of the workpiece. Therefore, when a rotary radial profiling to reduce the magnitude of the meridional stresses on the curved sections must be committed to increasing index k and a decrease in the angle θ to the site distribution and crimping the workpiece.
The calculation of the stress tensor components at a radius of curvature at the profiling roller radial profiling rotary wheel rims
Keywords: заготовка; деформация; поверхность тороидальная; оболочка; workpiece; distortion